2019
DOI: 10.21608/bvmj.2019.13775.1021
|View full text |Cite
|
Sign up to set email alerts
|

The impact of β glucan on the Immune Response of Broiler Chickens Vaccinated with NDV and AI H9V Vaccines

Abstract: To evaluate the effects of β glucan on innate and adaptive immune responses of broilers vaccinated for routine vaccination with Newcastle disease virus (NDV) and Avian Influenza H9N2 (AIV) vaccines. A total of 180 chicks of one-day old Hubbard local breedThey were divided into three groups (sixty chicks for each group). The first group fed with normal broiler diet without any additives and served as control group, while the other two groups consumed diets contained (200mg , 400mg pure β glucan /kg diet respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The increase in the oxidative burst was also reported by (Ott et al, 2018). Furthermore, (Abd El Tawab et al, 2019) also confirmed that there is an increase in glutathione (GSH) and a decrease in malondialdehyde (MDA) which is suggestive of the anti-oxidative effects of β-glucans in broiler chickens. Additionally, (Moon et al, 2016) stated that β-glucans can lessen the oxidative stress experienced by broiler chickens which will result in good quality meat.…”
Section: Anti-oxidative Properties Of β-Glucanssupporting
confidence: 70%
“…The increase in the oxidative burst was also reported by (Ott et al, 2018). Furthermore, (Abd El Tawab et al, 2019) also confirmed that there is an increase in glutathione (GSH) and a decrease in malondialdehyde (MDA) which is suggestive of the anti-oxidative effects of β-glucans in broiler chickens. Additionally, (Moon et al, 2016) stated that β-glucans can lessen the oxidative stress experienced by broiler chickens which will result in good quality meat.…”
Section: Anti-oxidative Properties Of β-Glucanssupporting
confidence: 70%
“…The expression of genes associated with antioxidants as affected by nucleotides and/or β-glucan supplementation were illustrated in Figs. (1)(2)(3). The findings revealed a significant increase in the expression of genes linked to antioxidants, inluding CAT, SOD, and GPx genes, in liver tissue in groups supplemented with nucleotides and β-glucan as opposed to other groups.…”
Section: Expression Of Genes Linked To Antioxidants In Hepatic Tissuementioning
confidence: 89%
“…Food and water were supplied ad libitum. As illustrated in table (1), a nutritionally balanced diet was administered to the chicks, adhering to the recommended nutrient levels for the Cobb 500 broiler strain. The nutrition schedule was divided into three stages during the experimental period: starter (days one to ten), grower (days eleven to twenty-four), and finisher (days twenty-five to thirty-five).…”
Section: Experimental Design and Managementmentioning
confidence: 99%